Publisher Correction: Sirt1 activator induces proangiogenic genes in preadipocytes to rescue insulin resistance in diet-induced obese mice - Allah Nawaz (Nature Portfolio, 2018)
A correction to this article has been published and is linked from the HTML and PDF versions of this paper. The error has not been fixed in the paper.